PERMASALAHAN TENTANG UPAYA POLRI DALAM MENENTUKAN LOCUS DELICTI YANG BELUM DIKETAHUI SECARA PASTI - Prasetiyo Abdi Utomo (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT If the scene is not known with certainty that the efforts made are Doing action by way of prosecution which is a technique of investigation it was revealed that the criminal case , where the techniques of this investigation will obtain answers to these questions in the field of investigation of a criminal case ; To conduct the interrogation of the reporting of events and people ask for information from witnesses , expert witnesses and witnesses who know the first time this criminal case . Despite the difference in area between the crime scene with the area where the discovery of the victim or the proceeds of crime not deter the police to uncover the criminal case , because although there is a difference region police still can mutually cooperate with each other . That despite the differences between the locus delicti region with the discovery of the victim or the proceeds of crime does not preclude the police to uncover the criminal case , because despite the differences in the area the police can still cooperate with each other